The role of wine in the heroic code: sacredness, politics and ξενία in Iliad and Odyssey (Circe de clásicos y modernos, 2020)
In the Homeric poems, wine appears as valuable merchandise and a drink of divine character by which human beings delight. Throughout both Iliadand Odyssey wine is presented by the poet as a central component in religious rites and, above all, is one of the essential elements of the banquet within the framework of the ξενία. The goal of this article is to approach the conceptualization of wine as an element of social and political cohesion in Homeric poems. First, I will investi-gate the poetic value that Homer attributes to wine in its different contexts, and then demonstrate its role as a po-litical device in the fulfillment of social norms governed by the sacredness of rites and the realization of the ξενία as observance of the divine mandates.
Keywords: wine; Homeric poems; politics; ξενία; sacredness